1996
DOI: 10.1103/physrevlett.77.4832
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of Colloidal Solutions

Abstract: The phase diagram of globular colloids is studied using a combined analytic and computational representation of the relevant chemical potentials. It is shown how the relative positions of the phase boundaries are related to the range of interaction and the number of contacts made per particle in the solid phase. The theory presented successfully describes the features of the phase diagrams observed in a wide variety of colloidal systems. [S0031-9007(96)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
277
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(293 citation statements)
references
References 24 publications
9
277
0
1
Order By: Relevance
“…The existence of a liquid protein phase in concentrated protein solutions, the multilayer stacks discussed here being one manifestation, has been dealt with in greater detail elsewhere, and it is the source of much current interest in the field of colloids as well as crystal growth (Asherie et al, 1996;Haas and Drenth, 1999;Kuznetsov et al, 1999b;Lui et al, 1995;Ten Wolde and Frenkel, 1997). It was one of the more unexpected results to emerge from AFM studies of macromolecular crystal growth.…”
Section: Mechanisms Of Crystal Growthmentioning
confidence: 88%
See 2 more Smart Citations
“…The existence of a liquid protein phase in concentrated protein solutions, the multilayer stacks discussed here being one manifestation, has been dealt with in greater detail elsewhere, and it is the source of much current interest in the field of colloids as well as crystal growth (Asherie et al, 1996;Haas and Drenth, 1999;Kuznetsov et al, 1999b;Lui et al, 1995;Ten Wolde and Frenkel, 1997). It was one of the more unexpected results to emerge from AFM studies of macromolecular crystal growth.…”
Section: Mechanisms Of Crystal Growthmentioning
confidence: 88%
“…Such a phenomenon fails, however, to explain the perfect alignment of all of the stacks with the underlying lattice and with one another. A second explanation, for which there is now substantial and persuasive evidence, suggests that they arise from liquid protein phase droplets that exist in concentrated macromolecular solutions (Asherie et al, 1996;Kuznetsov et al, 1998;Lui et al, 1995). These liquid protein phase droplets are composed of many thousands of molecules exhibiting short-range order, mediated principally by nonspecific hydrophobic interactions and random arrangements of hydrogen bonds.…”
Section: Mechanisms Of Crystal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase diagrams are used to characterize the interactions between macromolecules, including colloidal particles and proteins. 8,25,33,34 These studies have shown that the effective inter-protein interaction potential results from the complex interplay of both attractive and repulsive contributions. 35 Proteins are inherently anisotropic, since each surface exposed amino acid contributes to varying degrees to the overall net-interaction potential.…”
Section: Introductionmentioning
confidence: 99%
“…26,33,36,37 Liquid-liquid phase separation (LLPS) occurs for proteins interacting via short-ranged net attractive forces. 25,33,34 Indeed, the temperature at which LLPS occurs is sensitive to the strength of net attraction between proteins in solution and can be used to probe the relative changes in protein inter-particle interactions as a result of altered protein chemistry, changing solution conditions or the presence of a second protein type. 38,39 In this study, we experimentally assess the phase diagram for human gD-crystallin (HGD), which is a structural protein in the eye lens that undergoes LLPS due to short-ranged attractive interactions which dominate its behaviour at physiological pH (at the pI of the protein).…”
Section: Introductionmentioning
confidence: 99%